Cross-Sectional Examination of Agricultural Firms in Relation to the Leaders’ Attitude - Kerékjártó, Gábor (Acta Agraria Debreceniensis, 2003)
As a PhD student at the Management Department of Debrecen University my project was to find examine circumstances of agricultural business entities in connection with structural, social and economic changes. This topic is integral part of the research program „Functional Study of Business-Management”, specified the topic „Structural Management Researches”. My setting of objectives were to find any connection between changes and attitude of leaders. I tried to explore the direction, tightness and tendencies of these relations, to choose some special management-method, which ones are much more succesfull than the other ones during the change-managing process. The base of my experiences are the results of special questionnaires, which were sent to several member of different type of enterprises relating to agricultural activity.